Governar a educação, diversidade nacional e as cidadanias globalizadas na Grã-Bretanha - Clementina Marques Cardoso (Universidade do Minho, 2007)
This is an introductory contribution to the issue of social diversity aimed at demonstrating the use of classifications as an instrument of social policy and the importance of classifications as a component of processes of governance and management of social diversity in the Great-Britain. The second part of the article highlights the problems of using classifications and their consequences and discusses the main characteristics of and the contradictions present in the debate relating to the problematic of managing social diversity.